2018
DOI: 10.1016/j.micpath.2017.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus polysaccharides inhibit avian infectious bronchitis virus infection by regulating viral replication

Abstract: The avian coronavirus causes infectious bronchitis (IB), which is one of the most serious diseases affecting the avian industry worldwide. However, there are no effective strategies for controlling the IB virus (IBV) at present. Therefore, development of novel antiviral treatment strategies is urgently required. As reported, astragalus polysaccharides (APS) have potential antiviral effects against several viruses; however, the antiviral effect of APS against IBV remains unclear. In this study, we explored whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 28 publications
(42 reference statements)
2
38
0
1
Order By: Relevance
“…The major flavonoids of Astragalus are 3-O-β- d -glucoside, 2′-hydroxy-3′,4′-dimethoxyisoflavane-7-O-β- d -glycoside, 7,3′-dihydroxy-4′-methoxyisoflavone, 7,3-dimer-capto-4,1-methoxyisoflavone, 3-dimercapto-7,4,1-methoxyisoflavone, and kumatakenin (Lv et al 2011 ; Xiao et al 2004 ). A recent study showed that crude extracts of Astragalus are anti-inflammatory (Kim et al 2013 ), anti-viral (Zhang et al 2018 ), immunostimulatory (Zhang et al 2017 ), promote growth performance (Li et al 2018 ) and affects fecal microbiota of young hens (Qiao et al 2018a ). In recent years, fermentation has become a powerful tool for producing biological materials, degrading macromolecular material into small molecules, reducing the side effects associated with herbs such as Aristolochia plants, and introducing medicinal effects through biological modification (Lin and Chiang.…”
Section: Introductionmentioning
confidence: 99%
“…The major flavonoids of Astragalus are 3-O-β- d -glucoside, 2′-hydroxy-3′,4′-dimethoxyisoflavane-7-O-β- d -glycoside, 7,3′-dihydroxy-4′-methoxyisoflavone, 7,3-dimer-capto-4,1-methoxyisoflavone, 3-dimercapto-7,4,1-methoxyisoflavone, and kumatakenin (Lv et al 2011 ; Xiao et al 2004 ). A recent study showed that crude extracts of Astragalus are anti-inflammatory (Kim et al 2013 ), anti-viral (Zhang et al 2018 ), immunostimulatory (Zhang et al 2017 ), promote growth performance (Li et al 2018 ) and affects fecal microbiota of young hens (Qiao et al 2018a ). In recent years, fermentation has become a powerful tool for producing biological materials, degrading macromolecular material into small molecules, reducing the side effects associated with herbs such as Aristolochia plants, and introducing medicinal effects through biological modification (Lin and Chiang.…”
Section: Introductionmentioning
confidence: 99%
“…Astragalus membranaceus is the main component of Fangji Huangqi decoction. Pharmacological studies have shown that APS, as the main ingredient of Astragalus membranaceus, has various therapeutic functions, such as immune regulation [20,21], anti-inflammation [7,22], antioxidation [23], antivirus [24,25], antibacterial [26], lowering blood sugar [27], and protecting the liver [28] and kidney [29]. Furthermore, it has been reported that APS could prevent RA progression [8,30].…”
Section: Resultsmentioning
confidence: 99%
“…As a potent ROS scavenger, Salvia miltiorrhiza Bunge inhibited high glucose-induced oxidative stress, reduced the generation of ROS and mitochondrial depolarization (Sun, et al, 2018). Astragalus polysaccharide had antioxidant, antiviral activities and promoted pro-apoptosis (Zhang, et al, 2018). These may partially explain the mechanisms of anti-atherosclerotic effects of yixintongmai.…”
Section: Discussionmentioning
confidence: 99%